The Role of Kediri City Local Government in Handling Social Conflicts as a Foundation for National Security and Resilience - Anang Puji Utama; Tri Panca Titis Arbiansyah; Prihantoro, Mitro; Malik, Ichsan (International Journal of Education, Vocational and Social Science, 2025)
This study aims to provide a juridical review and analytical assessment of the role of local governments in managing social conflicts as a foundation for maintaining national security and resilience. The Kediri City Government, as the closest administrative structure to the community, plays a strategic role in conflict prevention, resolution, and post conflict recovery. The practical implementation of social conflict management still encounters several challenges, including budgetary limitations, suboptimal human resource capacity, weak inter agency coordination, inadequate dissemination of the Social Conflict Management, and limited community participation, particularly from customary and social institutions. Using a descriptive qualitative approach, this study employs in depth interviews, literature reviews, and policy analysis supported by relevant documents, legal frameworks, and prior research findings. The results reveal that the effectiveness of conflict management in Kediri City strongly depends on the integration of Social Conflict Management into regional development policies, capacity building for local officials, and the enhancement of coordination mechanisms between local agencies and vertical institutions. Furthermore, community empowerment and the revitalization of local social institutions are identified as crucial elements in establishing sustainable peace and social stability.